Effect of Trucking Distance on Sale Price of Beef Calf and Feeder Cattle Lots Sold Through Video Auctions from 2010 Through 2018 - E. D. McCabe; M. E. King; K. E. Fike; M. J. Smith; G. M. Rogers; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective was to determine effect of trucking distance on sale price of beef calf and feeder cattle lots sold through Superior Livestock Video Auctions from 2010 through 2018. Study Description:Data analyzed were collected from 211 livestock video auctions that included 42,043 beef calf and 19,680 feeder cattle lots delivered to 6 states (Colorado, Iowa, Kansas, Nebraska, Oklahoma, and Texas). Multiple regression models were used to evaluate the effect of factors, with trucking distance of main interest, on sale price of lots. Based on reported states of origin and delivery, lots were categorized into one of the following trucking distance categories: 1) within-state, 2) short-haul, 3) medium-haul, and 4) long-haul. Results:Beef calf lots hauled within-state sold for more ($169.24/cwt;P<0.0001) than other trucking distance categories. Long-haul calf lots sold for the lowest (P<0.0001) price ($166.70/cwt). Within-state and short-haul feeder cattle lots sold for the greatest (P<0.0001) price ($149.96 and $149.81/cwt, respectively). Long-haul feeder cattle lots sold for the lowest (P<0.0001) price, $148.43/cwt. The Bottom Line:These results indicate there is a price advantage for lots expected to be hauled shorter distances, likely because of cost and risk associated with transportation
Keywords: beef calf lots; feeder cattle lots; trucking distance